Effects of quercetin on the nicotine-induced oxidative status in male Wistar rats: study on c-reactive protein (CRP) and malondialdehyde (MDA) concentrations - Deri Riskiyanti Tallo Manafe; Denny Agustiningsih; . Prasetyastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTNicotine can cause atherosclerosis by activating nuclear factor-kB (NF-kB) pathway lead to induce proinflammatory cytokines release as C-reactive protein (CRP) main regulators. The increase of CRP can induce reactive oxygen species (ROS) and increase of malondialdehyde (MDA). Quercetin has been proven to have antiinflammatory and antioxidant effects. This study was conducted to evaluate effect of quercetin on serum CRP and MDA concentrations in rats induced by nicotine. This was a true experimental study with post test only control group design. Thirty six of male Wistar rats were divided into six groups. Group I as normal control received 1 mL/kg BW of NaCl 0.9% solution. Group II as negative control received 2 mg/kg BW of nicotine and Group III as positive control received 2 mg/kg BW of nicotine and atorvastatin at dose of 5 mg/kg BW. Group IV-VI as treatment groups received 2 mg/kg BW of nicotine and quercetin at dose of 25; 50 or 100 mg/kg BW, respectively. Nicotine was given subcutaneously whereas atorvastatin and quercetin were given orally once per day for 28 days, consecutively. Serum CRP and MDA concentrations were measured using Rat hs-CRP ELISA kit and TBARS assay kit, respectively. Data were analyzed using analysis of variance (ANOVA) continued using LSD post-hoc test. The results showed that quercetin reduced serum CRP and MDA concentrations in dose dependent manner. Serum CRP concentration on Group V (173.39 ± 34.85 ng/mL) and Group VI (114.15 ± 43.62 ng/mL) were significantly lower than that Group II (244.77 ± 37.95 ng/mL) (p<0.05). Furthermore, serum MDA concentration on Group IV (5.95 ± 0.11 mmol/mL), Group V (3.93 ± 0.09 mmol/mL) and Group VI (2.14 ± 0.09 mmol/mL) were significantly lower than that Group II (7.29 ± 0.06 mmol/mL) (p<0.05). In conclusion, quercetin reduces the nicotine-induced oxidative status in rats.